The Relationship Between Gratitude And Subjective Welfare In Students Of The Faculty Of Psychology And Educational Sciences Muhammadiyah University Sidoarjo: Hubungan Antara Kebersyukuran Dengan Kesejahteraan Subjektif Pada Mahasiswa Fakultas Psikologi Dan Ilmu Pendidikan Universitas Muhammadiyah Sidoarjo - Siti Uswatun Khasanah; Eko Hardi Ansyah (Universitas Muhammadiyah Sidoarjo, 2021)
Recently, students often experience stress due to various demands, such as college assignments and thesiss. This study aims to determine the relationship between gratitude and subjective well-being in students of the Faculty of Psychology and Education, Muhammadiyah Sidoarjo. The method in this study uses a correlational quantitative approach. The sample in this study were students of the Faculty of Psychology and Educational Sciences, Muhammadiyah University of Sidoarjo, totaling 299 students. The sampling technique was carried out by random sampling method. Data collection used two psychological scales with a Likert scale model for gratitude scale and a Positive Affect Negative Affect Schedule for subjective well-being scale. Data analysis using the product moment correlation test technique. The results of this study indicate that there is a significant relationship between gratitude and subjective well-being in students of the Faculty of Psychology and Education, University of Muhammadiyah Sidoarjo, with a correlation coefficient of 0.093 with a significance of 0.017 > 0.05. The determinant coefficient test shows a result of 0.006 (R Square), which explains that in this study, the gratitude variable has an effective effect of 0.6% on subjective well-being. The test results show the hypothesis can be accepted.